Wykonaj redukcję wyrazów podobnych i oblicz wartości liczbowe wyrażeń algebraicznych:

a) 3x - 4x + 2x - 5x + 7

dla x = -1
dla x = 0
dla x = 2,5

b) -3m - 4n + 3n + 5m

dla m = 1 i n = -2
dla m = -0,5 i n = 0,1

c) -13x + y + 23x - 20y + 6

dla x = 0,02 i y = - ³₁₉
dla x = 0 i y = 1

dam naj ;D

3

Odpowiedzi

2010-01-10T14:06:37+01:00
A) 3x-4x+2x-5x+7= -4x+7
dla x=-1
-4*(-1)+7=4+7=11

dla x=0
-4*0+7= 0+7=7

dla x=2,5
-4*2,5+7=-10+7=-3

b) -3m - 4n + 3n + 5m= 2m-n
dla m=1 , n=-2
2*1-(-2)= 2+2=4

dla m=-0,5 , n=0,1
2*(-0,5)-0,1= -1-0,1=-1,1



2010-01-10T14:10:34+01:00
A)
3x - 4x + 2x - 5x + 7= -4x + 7 = -4 * (-1) + 7 = 4+7=11
3x - 4x + 2x - 5x + 7= -4x + 7 = - 4 * 0 +7 = 7
3x - 4x + 2x - 5x + 7= -4x + 7 = - 4 * 2,5 + 7 = -3

b)
-3m - 4n + 3n + 5m = 2m-1n= 2 * 1 - 1*(-2 )= 2 - (-2) = 4
-3m - 4n + 3n + 5m = 2m-1n=2*(-0,5) -1*(0,1)= -1 -0,1 = -1,1

c)
-13x + y + 23x - 20y + 6= 10x - 19y + 6 = 10 * 0,02 - 19 * 3/19 +6=
0,2-3+6=3,2

-13x + y + 23x - 20y + 6= 10x - 19y + 6 =10*0 - 19*1 + 6 = 0-19+6=-13
Najlepsza Odpowiedź!
2010-01-10T14:12:18+01:00
A) 3x - 4x + 2x - 5x + 7 = -1x +2x-5x+7= -4x+ 7

-dla x = -1 -4 *(-1)+7= 4+ 7= 11
dla x = 0 -4*0 +7= 0+7=7
dla x = 2,5 -4 * 2,5 +7= -10 +7= -3


b) -3m - 4n + 3n + 5m = - 3m +5m -4n +3n= 2m - 1n

dla m = 1 i n = -2 2m-1n= 2 *1 - 1 *(-2)= 2 +2=4
dla m = -0,5 i n = 0,1 2m- 1n= 2 * (-0.5) - 0.1 = -1 - 0.1= 1.1

c) -13x + y + 23x - 20y + 6= 10x - 19y +6

dla x = 0,02 i y = - ³₁₉ 10 * 0.02 - 19 * - ³₁₉ +6 = 0.020
dla x = 0 i y = 1 10 * 0 -19 * 1 + 6= 0-19 +6= -19+6= - 13

³₁₉ - co to jest ?!